Photoreceptor ubiquitination by COP1 E3 ligase desensitizes phytochrome A signaling - Seo, Hak Soo (Cold Spring Harbor Laboratory Press, 2004)
Desensitization of activated receptors is an important mechanism for terminating signal transduction. Here we show that phytochrome (phy) A, a predominant photoreceptor for seedling deetiolation, colocalizes in nuclear bodies with CONSTITUTIVELY PHOTOMORPHOGENIC (COP) 1, a RING motif-containing E3 ligase. The phyA PAS domain interacts with the COP1 WD40 domain. Both the Pr and the Pfr forms of phyA, as well as the PHYA apoprotein, are ubiquitinated by COP1 in vitro. The phyA destruction rate is decreased in cop1 mutants and by expression of a COP1 RING motif mutant. Our results indicate that COP1 acts as an E3 ligase to regulate phyA signaling by targeting elimination of the phyA photoreceptor itself.